2013
DOI: 10.1002/art.37948
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐29a Protects Against Glucocorticoid‐Induced Bone Loss and Fragility in Rats by Orchestrating Bone Acquisition and Resorption

Abstract: MicroRNA-29a signaling protected against glucocorticoid-induced disturbance of Wnt and Dkk-1 actions and improved osteoblast differentiation and mineral acquisition. Promotion of miR-29a signaling is an alternative strategy for alleviating glucocorticoid-induced bone deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 49 publications
(59 reference statements)
5
85
1
3
Order By: Relevance
“…So far only miR-29a has been reported to ameliorate glucocorticoid-induced suppression of osteoblast differentiation by regulating Wnt/β-catenin pathway. 33,34 In this study, we found that overexpression of miR-216a can significantly rescue the suppressive effects of DEX on the osteoblast differentiation of hAMSCs, which suggested that therapeutic upregulation of miR-216a in MSCs may promote bone formation and even reverse osteoporosis. With the development of miRNA delivery system, which can Damage of the bone formation potential of MSCs is responsible for the bone loss incurred in aging and osteoporosis.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…So far only miR-29a has been reported to ameliorate glucocorticoid-induced suppression of osteoblast differentiation by regulating Wnt/β-catenin pathway. 33,34 In this study, we found that overexpression of miR-216a can significantly rescue the suppressive effects of DEX on the osteoblast differentiation of hAMSCs, which suggested that therapeutic upregulation of miR-216a in MSCs may promote bone formation and even reverse osteoporosis. With the development of miRNA delivery system, which can Damage of the bone formation potential of MSCs is responsible for the bone loss incurred in aging and osteoporosis.…”
Section: Discussionmentioning
confidence: 60%
“…[30][31][32] However, to date, only a few miRNAs have been reported to be antagonists for the suppression of glucocorticoids during osteogenic differentiation. 33,34 In this study, we revealed that miR-216a promotes the osteogenic differentiation of human adipose-derived MSCs (hAMSCs) in vitro and enhances bone formation in vivo. Moreover, we demonstrated that a high concentration of dexamethasone (DEX) inhibits osteogenic differentiation, whereas miR-216a antagonizes the suppressive effect of DEX on osteogenic differentiation.…”
mentioning
confidence: 96%
“…Interestingly, miR-29a, which had been previously shown to suppress Osteonectin during osteoblastogenesis, 36 was found to protect against glucocorticoid-induced bone loss, a frequent pathological repercussion that leads to decreased osteoblast survival and increased osteoclast activity. 37 Forced expression of miR-29a attenuated the effects of glucocorticoid treatment, increasing trabecular bone mass and decreasing cortical bone porosity.…”
Section: Mirna Regulation Of Other Bone-related Pathologiesmentioning
confidence: 99%
“…For example, a reduction in miRNA-29a expression, which interacts with Wnt signalling components and Dkk-1 during osteoblast differentiation was associated with GC-associated bone loss. Gain of miRNA-29a function by a miRNA-29a precursor (Wang et al 2013) attenuated the deleterious effects of GC treatment on bone mass, microarchitecture and biomechanical strength.…”
Section: Gcs and Their Mechanisms Gc-induced Osteoporosismentioning
confidence: 99%